Preferensi Agama dan Profesionalisme dalam Film The Endgame: Sebuah Analisis Wacana Kritis - Gaffar, Abdul (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Reformation is a milestone in the improvement of the Indonesian nation after being ruled by the new order for 32 years. This article discussed the dynamics of corruption and corruption eradication institutions in the film The endgame. This film revealed an effort to eliminate employees of the Corruption Eradication Commission (KPK) through the national insight test. The elimination was considered because they were radical and part of the Taliban police and those who handled major cases, but it was not explained whether KPK employees who passed the national insight test include those who handled major cases or not. The method used in this article is critical discourse analysis. critical discourse analysis is a method that effort to see the relationship between language and text and the social context in which language is used. The result of this study revealed that the film The Endgame did not reveal the fact that 75 KPK employees were removed with the national insight test. Instead of showing arguments that lead to the fact, this film tends to attack the parties involved in the national insight test, for example, the leaders of the KPK, the state civil service agency (BKN, and the compilers of questions in the test. Religious preference is used to legitimize the opinion that they are excluded because the religious preference. Professionalism was not a concern in this film.